KULTIVASI SPIRULINA PLATENSIS MENGGUNAKAN MEDIA WALNE DALAM SKALA LABORATORIUM - Aidil Fadli Ilhamdy; Jumsurizal; Darwin (Marinade, 2020)
This research was conducted in three stages: the first, prepared seawater to be sterilized for 2 days, which had been added with diluted chlorine and Na-thiosulfate. The second was preparation for cultivation on a small scale and for scale up on a large scale. The third was haversting Spirulina platensis when the cell density was at the peak of the growth curve (Optical density more than 0,5). The purpose of this study was to know the growth pattern of Spirulina platensis microalgae use walne media and to determine the ideal density of the microalgae growth until yhe haverst process. The results of the growth rate of Spirulina platensis, which were scaled to a scale of 80 liters using walne media, experienced very good cell growth, this can be seen from the increase in the amount of optical density (OD), temperature, and increased pH. achieve general standard values.